Suppression of Cross-Polarization of the Microstrip Integrated Balun-Fed Printed Dipole Antenna - Huang Jingjian; Zhang Xiaofa; Xie Shaoyi; Wu Weiwei; Yuan Naichang (International Journal of Antennas and Propagation, 2014)
The high cross-polarization of the microstrip integrated balun-fed printed dipole antenna cannot meet the demands of many engineering applications. This kind of antennas has high cross-polarization levels (about −20 dB). And we find that the high cross-polarization radiation is mainly produced by the microstrip integrated balun rather than the dipole itself. The very limited method to lower the cross-polarization level of this kind of antennas is to reduce the substrate thickness. In this paper, to improve the low cross-polarized performance, firstly, an equivalent model is presented to analyze the cross-polarization radiation. Secondly, a novel structure with low cross-polarization is proposed. The microstrip integrated balun is enclosed by a center slotted cavity. The E-field of the microstrip integrated balun is transformed parallel to the dipole arms by the slot, so the radiation of the cross-polarized component is suppressed. Measured results show that this structure can achieve a bandwidth wider than 40% while reducing the cross-polarization level to less than −35 dB within the frequency band.